A Comparative Study with regard to Swiss Law on the Effect of the Adoption System on the Best Interests of the Child - Ayşen Çilenti Konuralp (İstanbul Hukuk Mecmuası)
The adoption system under the Turkish Civil Code differs from the process under the Swiss Civil Code in many respects. Contrary to Swiss law, Turkish law has not adapted the full adoption system; instead, it maintains a simple, mixed legal system that incorporates aspects of the Swiss adoption system into Turkish law. Consequently, the filiation relationship between adopted and biological family continues in Turkish law, and the adoptees have the right of double heirship. This, however, can interfere with bonding between the minor and the adoptive parents because of continued emotional bonds with the biological family which limits the expected benefit from adoption. Legislator have recently amended the Swiss adoption system toward further benefit of the adopted minors, for instance by incorporating more careful evaluations of children’s psychological status as well as that of the adoptive parents during the adoption process. The absence of such amendments in Turkish law raises the question of whether the Turkish adoption system is sufficient for the best interests of the child. Thus, the legal problem worth discussing in terms of the legal status and the best interest of the child under Turkish adoption system rises. For this reason, the preconditions of adoption and the legal consequences for adopted children are here examined in relation to children’s best interest.